Vitamin D deficiency, insulin resistance, and ventricular hypertrophy in the early stages of chronic kidney disease. (12th September 2013) - Lai, Silvia; Coppola, Bettina; Dimko, Mira; Galani, Alessandro; Innico, Georgie; Frassetti, Nicla; Mariotti, Amalia
Abstract: Background : Chronic kidney disease (CKD) is associated with markedly increased cardiovascular (CV) risk. This increase is not fully explained by traditional CV risk factors but may in part be mediated by nontraditional risk factors, such as inadequate vitamin D (vit D) levels and insulin resistance (IR). Although IR is shown in nondiabetic CKD, its association with vit D deficiency and vascular disease in this population is unknown and what this study aims to investigate. Materials and methods : The study comprised 67 patients with CKD (eGFR ≥ 30 mL/min) and 15 healthy controls matched for age and sex. The phlogosis indexes, vit D levels, IR, carotid intima-media thickness (cIMT), and left ventricular mass index (LVMI) were measured. Results : In our study, the mean value of LVMI and cIMT was significantly higher in patients with eGFR ≥ 30 mL/min compared with controls ( p = 0.037 and p < 0.001). The IR and intact parathyroid hormone (iPTH) levels were increased in CKD patients, whereas the serum levels of vit D were significantly reduced ( p = 0.044, p = 0.012, p = 0.038). A positive correlation was found between LVMI and IR ( r = 0.704, p = 0.041) and a negative correlation was found between IR and vit D levels ( r = −0.238, p = 0.031). Conclusions : In our study, IR and vit D deficiency were found to be independent predictors of left ventricular hypertrophy and atherosclerotic disease. Vitamin D deficiency and IR are thus associated with increased CV risk. More novel approaches to improving IR and vit D supplementation in the CKD population might lead to potential strategies for preventing excess CV mortality.